(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
For decades, vesical stone has been removed by traditional cystolithotomy. It gives a big scar and adds considerable morbidity to the patient. Here we tried a new indigenous technique to remove the bladder stone with a laparoscopic grasper . The aim was to minimize the morbidity and an almost invisible scar to the patient. DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19469